Knowledge, awareness, and perception on mammogram screening and effecting factors among visitors at Hospital Melaka - Hamdan, Muhammad Amir; Khamis, Taha; Muhd Azmi, Nurul Fathihah; Ahmad, Hafizah (2016)
Nowadays, breast cancer is one of the killer diseases in Malaysia. One way to diagnose the cancer is through mammogram screening. However not many people are aware or know about mammogram. The purpose of this study is to determine the level of perception, awareness and knowledge about mammogram screening and the effecting factors among visitors of Hospital Melaka. Questionnaire had used to collect the information that needed. There were 200 respondents involved in this study and there are from visitors in Hospital Melaka. The questionnaire had two languages, English and Malay. Pilot test was used to know the people’s understanding towards the questionnaire. Data was analyzed by using Statistical Package Social Science (SPSS) for Window Version 18.0 Software. Researchers in this study used percentage to analyze the level of perception, awareness and knowledge about mammogram screening among visitors of Hospital Melaka. As a conclusion the result showed 104 (52%) of respondent have a low knowledge about mammogram while the remaining 96 (48%) respondents have a high knowledge about mammogram. For level of awareness, 108 (54%) of respondents have low awareness about mammogram screening test, while 92 (46.0%) of them have high awareness about mammogram. Result for perception of mammogram showed 97 (48.5%) of respondents believes that mammogram screening test is unimportant, while 103 (51.5%) of respondents believes that mammogram is important. From the finding, there is no difference level of knowledge between gender and ages. However there is a difference level of knowledge between employed and unemployed respondent. Secondly, there is a difference level of awareness between gender also for the employed and unemployed respondent. For the ages there is no difference level of awareness. Lastly, there is a difference level of perception between gender. Meanwhile, there is no difference level of perception between ages and for the employed and unemployed respondent.